Amniotic fluid embolism: A rare complication of second-trimester amniocentesis - Drukker, L; Sela, H; Ioscovich, A; Samueloff, A; Grisaru-Granovsky, S (Karger Publishers, 2016)
Amniotic fluid embolism occurring following diagnostic amniocentesis is extremely rare. Only 2 cases have been reported in the English literature over the past 55 years, the most recent one approximately 3 decades ago. We present a case of amniocentesis at 24 weeks' gestation that was performed as part of an evaluation of abnormal fetal ultrasound findings. Immediately following amniotic fluid aspiration, maternal hemodynamic collapse occurred, initially diagnosed and treated as anaphylactic shock. Shortly after initial therapy, coagulopathy was noted and amniotic fluid syndrome suspected. Rapid response restored maternal hemodynamic stability; however, the fetus had suffered fatal damage.